A High-Efficiency CuO/CeO2 Catalyst for Diclofenac Degradation in Fenton-Like System - Zhu, Jia; Zhang, Guangming; Xian, Guang; Zhang, Nan; Li, Jinwei (Frontiers in Chemistry, 2019)
An efficient Fenton-like catalyst CuO/CeO2 was synthesized using ultrasonic impregnation and used to remove diclofenac from water. The catalyst was characterized by N2 adsorption-desorption, SEM-EDS, XRD, HRTEM, Raman and XPS analyses. Results showed that CuO/CeO2 possessed large surface area, high porosity and fine elements dispersion. Cu was loaded in CeO2, which increased the oxygen vacancies. The exposed crystalline plane of CeO2 (200) was beneficial to the catalytic activity. The diclofenac removal experiment showed that there was a synergistic effect between CuO and CeO2, which might be caused by more oxygen vacancies generation and electronic interactions between Cu and Ce species. The experimental conditions were optimized, including pH, catalyst and H2O2 dosages, and 86.62% diclofenac removal was achieved. Diclofenac oxidation by OH and adsorbed oxygen species was the main mechanism for its removal in this Fenton-like system.